Patterns of wildlife hunting and trade by local communities in eastern Amazonian floodplains - Bastos da Silva, André; E. R. Pereyra, Paula; R. El Bizri, Hani; M. S. Souto, Wedson; Sá Leitão Barboza, Rafael (Ethnobiology and Conservation, 2022)
Local people living in the Amazon rainforest rely heavily on wild meat as a source of protein and income. While the patterns and drivers of wildlife hunting and trade by local communities are well-known for upland forests, such aspects have been poorly explored in Amazonian ﬂoodplains. This study aims to describe wild meat hunting and trade patterns and assess the hunting dynamics of local communities in Amazonian ﬂoodplain areas. For this purpose, we interviewed 121 hunters in 36 communities living in white-water ﬂooded forests in the lower Amazon River, Brazil. Thirty taxa were cited as hunted by interviewees, who used a repertoire of 13 hunting techniques. Aquatic and semi-aquatic taxa were the most prevalent, especially Hydrochoerus hydrochaeris, Cairina moschata, and Podocnemis uniﬁlis. Eight taxa were cited as traded; wild meat was sold at 2.57 ± 2.22 USD/kg, while eggs of birds and turtles were sold at 0.37 ± 0.27 USD/unit. We found an inverted-U relationship between the body mass and the number of citations per taxa, with species weighing between 10-40 kg presenting the highest number of citations. The hunting patterns found here are diﬀerent from those frequently found in the literature for upland environments. Understanding these hunting and trade patterns will help develop tailored wildlife conservation and management strategies for Amazonian ﬂoodplains.